A HIF-LIMD1 negative feedback mechanism mitigates the pro-tumorigenic effects of hypoxia - Foxler, Daniel E.; Bridge, Katherine S.; Foster, John G.; Grevitt, Paul; Curry, Sean; Shah, Kunal M.; Davidson, Kathryn M.; Nagano, Ai; Gadaleta, Emanuela; Rhys, Hefin I.; Kennedy, Paul T.; Hermida, Miguel A.; et al. (Wiley Open Access, 2018)
The adaptive cellular response to low oxygen tensions is mediated by the hypoxia inducible factors (HIFs), a family of heterodimeric transcription factors composed of HIF-α and β subunits. Prolonged HIF expression is a key contributor to cellular transformation, tumourigenesis and metastasis. As such, HIF degradation under hypoxic conditions is an essential homeostatic and tumour suppressive mechanism. LIMD1 complexes with PHD2 and VHL in physiological oxygen levels (normoxia) to facilitate proteasomal degradation of the HIF-α subunit. Here, we identify LIMD1 as a HIF-1 target gene, which mediates a previously uncharacterised, negative regulatory feedback mechanism for hypoxic HIF-α degradation by modulating PHD2-LIMD1- VHL complex formation. Hypoxic induction of LIMD1 expression results in increased HIF-α protein degradation, inhibiting HIF-1 target-gene expression, tumour growth and vascularisation. Furthermore, we report that copy number variation at the LIMD1 locus occurs in 47.1% of lung adenocarcinoma patients, correlates with enhanced expression of a HIF target gene signature and is a negative prognostic indicator. Taken together, our data open a new field of research into the aetiology, diagnosis and prognosis of LIMD1-negative lung cancers.